Role of liquid membrane hypothesis in the biological actions of beta-blockers - Nagappa, A.; Kole, P.L.; Pandi, P.V.; Girish, K.; Rahul, P.K.; Shanmukha, I. (2003)
The liquid membrane hypothesis in anti-hypertensive drugs, namely, propranolol, metoprolol and atenolol have been investigated. Adreneceptor antagonist drugs have been shown to generate liquid membranes in series with a supporting membrane. Transport through liquid membrane generated by lecithin, cholesterol and lecithin-cholesterol mixture has been studied in the presence of adreneceptor antagonists. The data indicate that the transport of cations and neurotransmitters of physiological importance is impeded in presence of the liquid membrane. Relevance of this observation to anti-hypertensive action and anti-arrythmic action of these drugs has been discussed. (C) 2002 Elsevier Science B.V. All rights reserved.